Biology of CD1- and MR1-restricted T cells. - Salio, M; Silk, J; Jones, E; Cerundolo, V (Annual Reviews Inc., 2014)
Over the past 15 years, investigators have shown that T lymphocytes can recognize not only peptides in the context of MHC class I and class II molecules but also foreign and self-lipids in association with the nonclassical MHC class I-like molecules, CD1 proteins. In this review, we describe the most recent events in the field, with particular emphasis on (a) structural and functional aspects of lipid presentation by CD1 molecules, (b) the development of CD1d-restricted invariant natural killer T (iNKT) cells and transcription factors required for their differentiation, (c) the ability of iNKT cells to modulate innate and adaptive immune responses through their cross talk with lymphoid and myeloid cells, and (d) MR1-restricted and group I (CD1a, CD1b, and CD1c)-restricted T cells.